Pengembangan Media Pembelajaran Multimedia Interaktif Berbasis Video Tutorial Editing Materi Media Audiovisual - Sigit Dwi Sucipto; Harlina Harlina; Rahmi Sofah (Bulletin of Counseling and Psychotherapy, 2022)
ADDIE model which consists of 5 stages, namely analysis (pre-test), design (making plans for implementing services and media scripts), development (making media, after the media is completed, then the researcher validates with three experts: material experts, media experts and linguists), implementation (small group test and field test), evaluation (post-test). Based on the results of the comments and suggestions given by the three experts, the results of the media are valid and worth testing. The results of the field test questionnaire, obtained a percentage of questionnaire scores of 87.4%. This percentage is in the range of 80% -100% which is included in the category of very practical whereas, the results of student guidance tests obtained results from all three aspects in the pre-test 42.6% and 66.4% post-test with an N-gain of 0.7 including in category (g) ≥0.70, which is high, it shows that interactive multimedia learning media based on video tutorials editing audiovisual media material is effective in IT media courses and guidance and innovation innovation at Sriwijaya University.